PNPase and RhlB Interact and Reduce the Cellular Availability of Oxidized RNA in Deinococcus radiodurans - Runhua Han; Jessie Jiang; Jaden Fang; Lydia M. Contreras (Microbiology Spectrum, 2022)
ABSTRACT 8-Oxo-7,8-dihydroguanine (8-oxoG) is a major RNA modification caused by oxidative stresses and has been implicated in carcinogenesis, neurodegeneration, and aging. Several RNA-binding proteins have been shown to have a binding preference for 8-oxoG-modified RNA in eukaryotes and protect cells from oxidative stress. To date, polynucleotide phosphorylase (PNPase) is one of the most well-characterized proteins in bacteria that recognize 8-oxoG-modified RNA, but how PNPase cooperates with other proteins to process oxidized RNA is still unclear. Here, we use RNA affinity chromatography and mass spectrometry to search for proteins that preferably bind 8-oxoG-modified RNA in Deinococcus radiodurans, an extremophilic bacterium with extraordinary resistance to oxidative stresses. We identified four proteins that preferably bind to oxidized RNA: PNPase (DR_2063), DEAD box RNA helicase (DR_0335/RhlB), ribosomal protein S1 (DR_1983/RpsA), and transcriptional termination factor (DR_1338/Rho). Among these proteins, PNPase and RhlB exhibit high-affinity binding to 8-oxoG-modified RNA in a dose-independent manner. Deletions of PNPase and RhlB caused increased sensitivity of D. radiodurans to oxidative stress. We further showed that PNPase and RhlB specifically reduce the cellular availability of 8-oxoG-modified RNA but have no effect on oxidized DNA. Importantly, PNPase directly interacts with RhlB in D. radiodurans; however, no additional phenotypic effect was observed for the double deletion of pnp and rhlB compared to the single deletions. Overall, our findings suggest the roles of PNPase and RhlB in targeting 8-oxoG-modified RNAs and thereby constitute an important component of D. radiodurans resistance to oxidative stress. IMPORTANCE Oxidative RNA damage can be caused by oxidative stress, such as hydrogen peroxide, ionizing radiation, and antibiotic treatment. 8-oxo-7,8-dihydroguanine (8-oxoG), a major type of oxidized RNA, is highly mutagenic and participates in a variety of disease occurrences and development. Although several proteins have been identified to recognize 8-oxoG-modified RNA, the knowledge of how RNA oxidative damage is controlled largely remains unclear, especially in nonmodel organisms. In this study, we identified four RNA binding proteins that show higher binding affinity to 8-oxoG-modified RNA compared to unmodified RNA in the extremophilic bacterium Deinococcus radiodurans, which can endure high levels of oxidative stress. Two of the proteins, polynucleotide phosphorylase (PNPase) and DEAD-box RNA helicase (RhlB), interact with each other and reduce the cellular availability of 8-oxoG-modified RNA under oxidative stress. As such, this work contributes to our understanding of how RNA oxidation is influenced by RNA binding proteins in bacteria.